Flower patterns improve foraging efficiency in bumblebees by guiding approach flight and landing. (18th January 2023) - Richter, Robin; Dietz, Alexander; Foster, James; Spaethe, Johannes; Stöckl, Anna
Abstract: Colourful patterns on flowers are thought to benefit both pollinators and the plants they visit, by increasing the plants' pollination success via an increased foraging efficiency of the pollinators. This increased efficiency is assumed to result from a guidance effect of the flower patterns, correspondingly termed 'nectar guides', which indicate the position of the nectary to visiting pollinators, thus reducing their flower handling time. Although it is well established that flower patterns play an important role in flower choice, the mechanisms by which they improve the foraging efficiency of flower‐visiting insects remain poorly understood. In this study, we quantified the contributions of patterns to all phases of flower interaction in the buff‐tailed bumblebee Bombus terrestris . We analysed the bees' flight paths, as well as landing positions and walking tracks on artificial flowers with different pattern types. We reveal that flower patterns reduced the overall flower handling time of the bees by up to 30%, by guiding their approach flight, landing positions and departure decisions. Surprisingly, we observed no improvement in nectary discovery time after the bees landed on the flower. Since we tested experienced foragers, which represent the majority of insect pollinators active in nature, the newly described nectary‐independent guidance effects of flower patterns are of high ecological relevance. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.